2010
DOI: 10.1016/j.jkss.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Some asymptotic properties for a smooth kernel estimator of the conditional mode under random censorship

Abstract: a b s t r a c tLet (T i ) 1≤i≤n be a sample of independent and identically distributed (iid) random variables (rv) of interest and (X i ) 1≤i≤n be a corresponding sample of covariates. In censorship models the rv T is subject to random censoring by another rv C . Let θ (x) be the conditional mode function of the density of T given X = x. In this work we define a new smooth kernel estimatorθ n (x) of θ (x) and establish its almost sure convergence and asymptotic normality.An application to prediction and confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Equation has been generalized to the case of censored response variables (Khardani, Lemdani, & Saïd, , ; Ould‐Saïd & Cai, ). Suppose that instead of observing the response variables Y 1 , ⋯, Y n , we observe T i = min { Y i , C i } and an indicator δ i = I ( T i = Y i ) that informs whether Y i is observed or not and C i is a random variable that is independent of X i and Y i .…”
Section: Modal Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation has been generalized to the case of censored response variables (Khardani, Lemdani, & Saïd, , ; Ould‐Saïd & Cai, ). Suppose that instead of observing the response variables Y 1 , ⋯, Y n , we observe T i = min { Y i , C i } and an indicator δ i = I ( T i = Y i ) that informs whether Y i is observed or not and C i is a random variable that is independent of X i and Y i .…”
Section: Modal Regressionmentioning
confidence: 99%
“…Under the assumptions on conditional density, the covariate is more responsible for the smoothing effect than the response. Various studies have reported the convergence of unimodal regression with dependent covariates (Attaoui, 2014;Collomb et al, 1986;Dabo-Niang & Laksaci, 2010;Khardani et al, 2010Khardani et al, , 2011Ould-Saïd, 1993, 1997Ould-Saïd & Cai, 2005). Strong consistency was investigated in Collomb et al (1986)) and Ould-Saïd (1993, 1997).…”
Section: Unimodal Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate estimator of the conditional df F(t|x) for censored data is, then, obtained by adapting Equation (5) in order to put more emphasis on large values of the interest random variable T which are more censored than a small one. Based on the same idea as in Carbonez, Downloaded by [Selcuk Universitesi] at 11:29 03 January 2015 Györfi, and van der Meulen (1995) and Khardani, Lemdani, and Ould-Said (2010), we consider the following weights:…”
Section: A Nonparametric Estimator Of the Conditional Quantilementioning
confidence: 99%
“…Much research has been devoted to the estimation of the unconditional and conditional mode. We focus on recent papers based on conditional mode estimators to mention [25,29,22,26,4,9,15,16].…”
Section: Introductionmentioning
confidence: 99%